Moulds in biodeterioration of technical materials - Gutarowska, Beata (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2014)
Moulds are microorganisms which play the key role in biodeterioration of technical materials which results from their physiological features and metabolism. Technical materials constitute the source of carbon and energy (wood, paper, textiles, fuels, leather) or the surface for fungal growth (bricks, stone, metal, glass). Moulds characterized by a high biodeterioration activity – enzymatic and acidic, belong mainly to the following genera: Aspergillus, Penicillium, Trichoderma, Cladosporium, Paecilomyces and Chaetomium. Members of some taxa (besides the aforementioned also e.g. Stachybotrys, Alternaria, Epidermophyton, Microsporum, Scopulariopsis, Trichophyton) growing on technical substances and producing allergens and mycotoxins cause health hazards. Therefore, basing on the knowledge about conditions for mould development and biodeterioration mechanisms, we should appropriately preserve materials against mould growth. Looking for new disinfection methods safe for technical substances in order to inhibit mould growth is also important. Protective applications of biocides should be limited only to materials most sensitive to biodeterioration (paper, textiles, fuels, paints). On the one hand we should take into consideration environmental protection, on the other production of durable, biodegradable materials ensuring the product life cycle.